2019
DOI: 10.3390/ijerph16173128
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals’ Knowledge of Probiotics: An International Survey

Abstract: The objective of this study was to survey health professionals to investigate their knowledge of probiotics. An online survey was conducted to gather data on the knowledge of health professionals. The online survey was distributed via email and social media platforms using snowball sampling. A total of 1066 health professionals (859; 80.6% female) from 30 countries responded to the survey. Most of the respondents evaluated their knowledge of probiotics as medium (36.4%) or good (36.2%). Only 8.9% of the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
59
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 57 publications
13
59
1
3
Order By: Relevance
“…In response to the question of how respondents prescribed probiotics, most (58%) reported that probiotics should be taken before a meal with no signi cant difference P-value among pediatricians. Similar to the observations by Tompkins et al, Sabina et al con rmed the highest survival of probiotics if given with a meal or before a meal, and the lowest survival if taken after a meal [7,17]. These results emphasize the importance for healthcare professionals to be properly educated and updated on probiotics because improved knowledge about probiotics would lead to increased prescriptive con dence [16].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In response to the question of how respondents prescribed probiotics, most (58%) reported that probiotics should be taken before a meal with no signi cant difference P-value among pediatricians. Similar to the observations by Tompkins et al, Sabina et al con rmed the highest survival of probiotics if given with a meal or before a meal, and the lowest survival if taken after a meal [7,17]. These results emphasize the importance for healthcare professionals to be properly educated and updated on probiotics because improved knowledge about probiotics would lead to increased prescriptive con dence [16].…”
Section: Discussionsupporting
confidence: 70%
“…Despite the widespread and easily accessible evidence that supports the bene ts of probiotic use, health professionals may hesitate to recommend probiotics to patients when they receive con icting messages [6]. Health professionals may have di culties in processing large volumes of information that are generated by commercial enterprises about the bene ts and use of probiotics [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the question of how respondents prescribed probiotics, majority (58%) reported that probiotics should be taken before a meal. Similar to the observations by Tompkins et al and Sabina et al con rmed the highest survival of probiotics if given with a meal or before a meal, and the lowest survival if taken after a meal [7,17]. These results emphasize the importance for healthcare professionals to be properly educated and updated on probiotics because improved knowledge about probiotics would lead to increased prescriptive con dence [16].…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the observations by Tompkins et al and Sabina et al con rmed the highest survival of probiotics if given with a meal or before a meal, and the lowest survival if taken after a meal [7,17]. These results emphasize the importance for healthcare professionals to be properly educated and updated on probiotics because improved knowledge about probiotics would lead to increased prescriptive con dence [16].…”
Section: Discussionsupporting
confidence: 86%